Investigation on the Effects of Additive on Performance and Photostability of PCDTBT:PC71BM Solar Cells - Endale Tsegaye Mohammed; Bedasa Abdisa Gonfa; Fedlu Kedir; Teketel Yohannes Anshebo (International Journal of Photoenergy)
In this work, the effect of DIM on the PCE and photostability of PCDTBT:PC71BM PSCs was investigated. DIM is an effective additive in a BHJ PCDTBT:PC71BM solar cell since it fulfills the requirement of a selective PC71BM dissolution. PCE of the device based on PCDTBT:PC71BM processed with DIM is higher than that of the reference device. In terms of the device stability, the PSCs processed with DIM showed poor stability at longer light exposure time. For the device without DIM especially as the light exposure time was increased, the device stability was better because the PCDTBT could be shielded from air by an aggregated PC71BM layer. For the PCDTBT:PC71BM device processed with DIM, the results obtained from J‐V measurement indicates that it has a lower recombination rate. The result from IS measurement shows that for pristine PCDTBT:PC71BM devices with 3% DIM, the active layer resistance is lower compared to the device without DIM. However, after irradiating the device for 5 hr, the resistance of the device processed with DIM is higher and it is consistent with decreased PCE of the aged device.